2010
DOI: 10.1080/13546801003737157
|View full text |Cite
|
Sign up to set email alerts
|

I see happy people: Attention bias towards happy but not angry facial expressions in Williams syndrome

Abstract: Introduction: Observations of behaviour and research using eye-tracking technology have

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
62
6
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(89 citation statements)
references
References 49 publications
18
62
6
3
Order By: Relevance
“…Studies that have employed eye tracking techniques have provided evidence that individuals with WS demonstrate a reduced ability to disengage attention from the eye region of a face when compared to mental-age (MA) matched controls Riby & Hancock, 2009). In addition, emotional expressions of faces have been shown to influence attention allocation, with positive (happy) emotions yielding greater visual attention than negative emotions (fearful, angry) in faces (Dodd & Porter, 2010;Plesa-Skwerer, Faja, Schofield, Verbalis, & Tager-Flusberg, 2006;Santos, Silva, Rosset, & Deruelle, 2010). The findings of atypical attention to positive emotional faces, specifically the eye region of faces in WS, are consistent with previous evidence of the role of the amygdala in directing visual attention (Gamer & Buechel, 2009;Gamer, Zurowski, & Buechel, 2010).…”
supporting
confidence: 81%
See 1 more Smart Citation
“…Studies that have employed eye tracking techniques have provided evidence that individuals with WS demonstrate a reduced ability to disengage attention from the eye region of a face when compared to mental-age (MA) matched controls Riby & Hancock, 2009). In addition, emotional expressions of faces have been shown to influence attention allocation, with positive (happy) emotions yielding greater visual attention than negative emotions (fearful, angry) in faces (Dodd & Porter, 2010;Plesa-Skwerer, Faja, Schofield, Verbalis, & Tager-Flusberg, 2006;Santos, Silva, Rosset, & Deruelle, 2010). The findings of atypical attention to positive emotional faces, specifically the eye region of faces in WS, are consistent with previous evidence of the role of the amygdala in directing visual attention (Gamer & Buechel, 2009;Gamer, Zurowski, & Buechel, 2010).…”
supporting
confidence: 81%
“…Thus the aims of the current study were threefold: firstly, we aimed to examine the interplay between visual attention and emotional facial expressions in adolescents and adults with WS. Consistent with previous studies showing greater attention for happy faces in WS (Dodd & Porter, 2010;Porter et al, 2010); we hypothesised that individuals with WS would show greater visual attention to happy facial expressions relative to both mental age (MA) and chronological age (CA) matched controls. Secondly, we aimed to investigate visual attention in relation to specific regions within emotionally expressive faces (e.g.…”
Section: Current Studysupporting
confidence: 65%
“…discrimination of facial expressions 46 and judgment of trustworthiness from faces, 48 is interesting in light of existing evidence showing that individuals with WBS have difficulty identifying facial emotional expressions [12][13][14] and that they tend to perceive unfamiliar faces abnormally positively. 7 In our study, individuals with WBS showed hypoactivation in the posterior region of the primary visual cortex, corresponding to foveal vision, as well as absence of activation in the right OFA.…”
Section: J Psychiatry Neurosci 2016;41(3)mentioning
confidence: 99%
“…If the patterns of amygdala activation found in previous research are genuinely associated with abnormalities in attentional deployment in WS, an attention bias for images depicting non-social threat would also be expected. The present research addresses this hypothesis using a dot-probe task based on that used by Dodd and Porter (2010). The dot-probe task is one of the most commonly used paradigms for assessing attention bias (Bar-Haim, Lamy, Pergamin, Bakermans-Kranenburg, & van Ijzendoorn, 2007).…”
Section: 1mentioning
confidence: 99%
“…Two recent studies have found initial support for this hypothesis. Dodd and Porter (2010) used a dot-probe paradigm (described below) and found that individuals with WS were biased to attend to happy faces but not to angry faces and Santos et al (2010) found decreased detection of angry faces in WS using a visual search task compared to typically developing individuals. Both of these findings are consistent with the patterns of amygdala activation reported for social stimuli, outlined above (Meyer-Lindenberg et al, 2005;Haas et al, 2009).…”
Section: 1mentioning
confidence: 99%